CuS@BSA-NB2 Nanoparticles for HER2-Targeted Photothermal Therapy - Ying, Ming; Li, Qin; Wu, Jingbo; Jiang, Yihang; Xu, Zhourui; Ma, Mingze; Xu, Gaixia (Frontiers in Pharmacology, 2022)
Breast cancer is characterized by the uncontrolled proliferation of breast epithelial cells under the action of a variety of carcinogens. Although HER2-targeted therapy is currently one of the most effective treatment options for breast cancer patiens difficult to make the following treatment plan for patients with anti-HER2 targeted drugs resistance. In this work, we prepared a novel CuS@BSA-NB2 nanoparticles (NPs) for breast cancer photothermal therapy (PTT). The NPs had good biocompatibility due to the BSA encapsulationg and excellent targeting to HER2 because of nanobody 2 (NB2). Under 808 nm laser irradiation, CuS@BSA-NB2 NPs had high photothermal conversion efficiency and photothermal stability. Meanwhile, we constructed a stable cell line of MDA-MB-231/HER2 with high expression of HER2 protein. Immunofluorescence assay showed that CuS@BSA-NB2 NPs can specifically enriched in MDA-MB-231/HER2 cells. Furthermore, CuS@BSA-NB2 NPs had shown a more significant photothermal treatment effect than CuS@BSA under certain treatment conditions for MDA-MB-231/HER2. In addition, the cytotoxicity assay demonstrated that CuS@BSA-NB2 NPs had a low toxicity for MDA-MB-231/HER2 cells. The above results suggested that CuS@BSA-NB2 NPs were great photothermal therapeutic agents to reduce malignant proliferation of breast epithelial cells and have potential for breast cancer therapy.